PEMBUATAN CHOCO CHIPS COOKIES MENGGUNAKAN TEPUNG TERIGU DAN TEPUNG UBI JALAR UNGU - tasya syaharani; Yulira Rahma Indah; Yen Polisda (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2023)
Purple sweet potatoes are rich in dietary fiber, minerals, vitamins and antioxidants. Purple sweet potatoes can be processed into flour made directly from crushed and dried purple. Its bread crumbs have its moisture removed. With such benefits, this article aims at exploring the experiment results of choco chip cookies with purple sweet potato flour as one of the alternatives to make cookies as it has been used for many years as snacks. The rationale for experimenting it into cookies because cookies are everyone's favorite. They are types of biscuits made from a soft and high-fat dough, and the characteristics of cookies are their crunchy texture and delicious taste. The cookies in this experiment were added by choco chips since they are of all ages' tastes. The control group was choco chip cookies with wheat flour. The choco chips both with wheat flour (control group) and with purple sweet potato flour (experiment group) were tested by the organoleptic test format by conducting a level test and a hedonic test. The level test was carried out with the aim of knowing the differences in shape, color, texture, and taste. The cookies were tested by ten panelists whose educational background is pastry. Organoleptic tests proved that 10 panelists preferred wheat flour cookies. The significant difference of the organoleptic test was in taste. Cookies made with purple sweet potato flour were a little bit licking because purple sweet potatoes are rich in fiber. The results of this study suggest that snacking purple sweet potato cookies will be more tasty and yummy with a glass of lemon juice.